STUDENTS’ OPINION TO THE IMPLEMENTATION OF PEER ASSESMENT - Gartika Pandu Buana (Eltin Journal : Journal of English Language Teaching in Indonesia, 2016)
As alternative assessment, peer assessment offers some advantages for teaching and learning process. Some experts believe that it can enhance students’ motivation,autonomy, and responsibility. This study aims to investigate students’ opinion to theimplementation of peer assessment. This study was qualitative. The respondents of thisstudy are second semester students at one of University in Bandung. The collected datais obtained through questionnaire. The data gained is categorized and analyzed based onthe some theories relating to peer assessment. Regarding the result, it is found thatbasically the students have positive response to the implementation of peer assessment.This is because of the potential benefits offered from peer assessment. Students perceivethat it helps them to evaluate their ability in speaking English, enhance their intrinsicmotivation, improve their critical thinking, and recognize the assessment criteria. Thisfinding indicates that peer assessment is worthwhile to be conducted in assessingstudents’ oral skill. Keywords: students' opinion, peer assessment, oral skill